The Market Orientation and Performance Relationship: An Empirical Study in Private Universities - Sefnedi Sefnedi (Universitas Pelita Harapan, 2017)
This study examines the empirical link between three dimensions of market orientation, namely, student orientation, competitor orientation and inter-functional coordination, and private university performance in Kopertis X. The study was based on an empirical investigation of private universities located in Indonesia’s provinces of West Sumatera, Riau, Jambi, and Riau Islands. The primary data for the study were collected from a self-administered mail survey of 237 questionnaires from the private university resulting in a sample of 114 usable responses being returned. From the application of the multiple regression analysis it was concluded that all three dimensions of market orientation had a significant impact on private university performance. Student orientation as a predictor variable is the strongest predictor of private university performance then followed by competitor orientation, and inter-functional coordination.Bahasa Indonesia Abstrak: Penelitian ini menguji hubungan empiris antara tiga dimensi orientasi pasar, yaitu, orientasi mahasiswa, orientasi pesaing dan koordinasi antar-fungsional dan kinerja perguruan tinggi swasta di Kopertis X. Penelitian ini didasarkan pada penyelidikan empiris pada universitas swasta yang berada di provinsi Sumatera Barat, Riau, Jambi, dan Kepulaian Riau. Data primer dikumpulkan dari survei dimana dari 237 kuesioner yang disebarkan pada universitas swasta, diperoleh 114 kuesioner yang dikembalikan dan dapat digunakan sebagai sampel. Berdasarkan hasil analisis regresi berganda dapat disimpulkan bahwa ketiga dimensi orientasi pasar memiliki dampak yang signifikan terhadap kinerja perguruan tinggi swasta. Orientasi mahasiswa sebagai variabel prediktor terkuat terhadap kinerja perguruan tinggi swasta kemudian diikuti oleh orientasi pesaing, dan koordinasi antar-fungsional.